The influence offwilliam'ss flexionnexercissonnthe Intensityyoffmentallpain (Dismenore)) Onnjuniorrhighhschoollstudents - Rehana Rehana; Nurul Komariah; Dina Nurul Fadilah (CV. AFDIFAL MAJU BERKAH, 2023)
Dysmenorrhea is pain in the lower abdomen that occurs when a woman experiences her menstrual cycle. Continuous pain makes the sufferer unable to move, especially in young women so that it can affect learning activities and often even causes her to be absent frommschool. Handling dysmenorrhea is very important to do. One type of non-pharmacological therapy to treat menstrual pain is to use William's Flexion Exercise which is an exercise program aimeddat stretching the posterior muscles and also increasing the strength of the lower abdominal and lumbar muscles so that menstrual painncan be reduced.To determine the effect of William's Flexion Exercises on reducing menstrual pain (Dysmenorrhea) in State Middle School 45 studentssPalembang in 2023. This research is a quantitativeestudy using a pre-experimental design with a one group pretest-posttest design approach. Sampling in this study used a purposive sampling technique with the slovin formula of 700respondents. The measuring instrument uses the Numeric Rating Scale (NRS) which has a sensitivityyvalue of 93%. Theeresults showed that the median value of menstrual pain before the intervention was 4.00 (1-6), while the median value after the intervention was 1.50 (0-5). Statistical tests using the Wilcoxon test obtained a significance value of ρ Value = 0.000 (ρ ≤ 0.05) which indicated that there was a significant effect of menstrual pain before and after the intervention of William's Flexion Exercise. There is a significantteffect of William's Flexion Exercises on the intensity of menstrual painn(dysmenorrhea) in students at SMP Negeri 45 Palembang. It is hoped that William's Flexion Exercise can be an alternativeeto reducing menstrual pain in students.